(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3CMeO Hf YHOGdbGOQ Hf CMeO Hf ecJhe Hf CMeO Hf eMeO Hf oSdje GdbjSj s)
(3ChdgG (B:s
(3hHYO, aEf cJGH JSgjd GdahGFO GHf eGdc ebje OeTb, QMeg Gddg s
(3BNQgG (B:s
(3hefg eNJda ajg, hSjCJj Pdc YfO PcQ GdQhGHW Je GdeLdO GdChd hjJdhg aj GdKGfj bhdg(B: (3ef heG aj GddaX GdeaQO s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g``s
(3aj GdeYgO GdLRA GdYGTQ efgs
(3GfXQg aj GdLRA GdChd Qbe (B65 (3fMh h(B66 (3fMh ecQQI efgGs
(3fSNI KGdKI s
(3fSNI ajgG VHW hgj Yf fSNI GdeDdas
(3HChdgG Jedc (B986(3g`` s
Keywords: (3GdfMhs